Proof-Carrying Hardware: Concept and Prototype Tool Flow for Online Verification - Stephanie Drzevitzky; Uwe Kastens; Marco Platzner (International Journal of Reconfigurable Computing)
Dynamically reconfigurable hardware combines hardware performance with software-like flexibility and finds increasing use in networked systems. The capability to load hardware modules at runtime provides these systems with an unparalleled degree of adaptivity but at the same time poses new challenges for security and safety. In this paper, we elaborate on the presentation of proof carrying hardware (PCH) as a novel approach to reconfigurable system security. PCH takes a key concept from software security, known as proof-carrying code, into the reconfigurable hardware domain. We outline the PCH concept and discuss runtime combinational equivalence checking as a first online verification problem applying the concept. We present a prototype tool flow and experimental results demonstrating the feasibility and potential of the PCH approach.